DA`WAH THROUGH ONLINE GAME APPLICATIONS (STUDY OF THE DA'WAH STRATEGY OF HAGO FRIENDS OF RELIGION) - Lukman; Kamilatun Nisa (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2022)
Research Objectives: To find out and describe Hago Friends of Religion's da'wah strategy in spreading Islam through the Hago online game application. Research Methods: Qualitative. Research Results: Hago Friends of Religion in their da'wah through the online game application Hago does the following things; strengthening effective management structures, presenting 24-hour da'wah content, namely morning migration motivation with Hago Friends of Religion, Morning Islamic study with Hago Friends of Religion, One day one juz, Live Evening Reflection with Hago Friends of Religion, Recitation of the holy verses of Al- Qur`an. Presentation of weekly or yearly content, namely Baca Rathib & Al-Kahf, Fadhilah of the Month of Muharram, Maulid Nabi Muhammad ﷺ, Religious month of Ramadan, and weekly evaluations.